The Homeopathic Approach to Tinea: Insights from Clinical Repertory (Homoeopathy for All, 2024)
The goal of this article was to offer  an updated narrative review focusing  on the assessment, diagnosis, and  treatment of tinea infections.
Keywords: Tinea; Ringworm; Homoeopathy; Clinical repertory